2015
DOI: 10.1371/journal.pone.0127351
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Changes in White Matter Microstructure after a Day of Waking and Sleep Deprivation

Abstract: BackgroundElucidating the neurobiological effects of sleep and waking remains an important goal of the neurosciences. Recently, animal studies indicated that sleep is important for cell membrane and myelin maintenance in the brain and that these structures are particularly susceptible to insufficient sleep. Here, we tested the hypothesis that a day of waking and sleep deprivation would be associated with changes in diffusion tensor imaging (DTI) indices of white matter microstructure sensitive to axonal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 66 publications
8
80
3
Order By: Relevance
“…Therefore, it is possible that the lack of significant associations with measures of persistent poor sleep may reflect limitations associated with the Jenkins Sleep Scale. In addition, since short‐term sleep deprivation has been associated with impaired performance in tests of attention, processing speed, working memory and short‐term memory [Lim and Dinges, ], as well as widespread fractional anisotropy decreases [Elvsåshagen et al, ], it is possible that our results reflect short‐term, potentially reversible, mechanisms associated with poor sleep.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is possible that the lack of significant associations with measures of persistent poor sleep may reflect limitations associated with the Jenkins Sleep Scale. In addition, since short‐term sleep deprivation has been associated with impaired performance in tests of attention, processing speed, working memory and short‐term memory [Lim and Dinges, ], as well as widespread fractional anisotropy decreases [Elvsåshagen et al, ], it is possible that our results reflect short‐term, potentially reversible, mechanisms associated with poor sleep.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, sleep disturbance is associated with distinct alterations in default mode network functional connectivity in brain regions underpinning salient memory and sleep systems . More specifically, sleep deprivation caused widespread changes in white matter (WM) microstructure . Therefore, previous studies have shown that sleep disturbance was associated with brain abnormalities .…”
Section: Introductionmentioning
confidence: 99%
“…One study excluded dehydration as the possible culprit (Vogel et al, ). It is known that WM microstructure can be affected by a variety of factors, including sleep deprivation (Elvsåshagen et al, ) and fasting (Bakan et al, ). In sum, despite inconsistencies studies strongly suggest the presence of WM microstructure alterations in acutely ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…One study excluded dehydration as the possible culprit (Vogel et al, 2016). It is known that WM microstructure can be affected by a variety of factors, including sleep deprivation (Elvsåshagen et al, 2015) and fasting (Bakan et al, 2015).…”
mentioning
confidence: 99%